The Current Situation and Prospect of Global Railway Technology Development from a Multidimensional Perspective - SHANG Jin; HAN Lu; HAN Lijun; LIU Gui; LI Jun (Kongzhi Yu Xinxi Jishu)
In order to clarify the current situation and trend of the railway development, analyses from multiple perspectives covering policy, market, intellectual property and international standard were made. The results show that the development direction of the global railway science and technology is converging to "safety, efficiency, green, intelligence and interconnection" which results in increasingly intense competition between countries and regions. It suggested that the future work should focus on refining the research organization mechanism, globalization of research resources, research on applicable technologies of segment-market and research on fundamental and transverse technologies.